Tumor-Associated Macrophages: Key Players in Triple-Negative Breast Cancer - Qiu, Xia; Zhao, Tianjiao; Luo, Ran; Qiu, Ran; Li, Zhaoming (Frontiers in Oncology, 2022)
Triple negative breast cancer (TNBC) refers to the subtype of breast cancer which is negative for ER, PR, and HER-2 receptors. Tumor-associated macrophages (TAMs) refer to the leukocyte infiltrating tumor, derived from circulating blood mononuclear cells and differentiating into macrophages after exuding tissues. TAMs are divided into typical activated M1 subtype and alternately activated M2 subtype, which have different expressions of receptors, cytokines and chemokines. M1 is characterized by expressing a large amount of inducible nitric oxide synthase and TNF-α, and exert anti-tumor activity by promoting pro-inflammatory and immune responses. M2 usually expresses Arginase 1 and high levels of cytokines, growth factors and proteases to support their carcinogenic function. Recent studies demonstrate that TAMs participate in the process of TNBC from occurrence to metastasis, and might serve as potential biomarkers for prognosis prediction.